Esg and Dividend Policy in Indonesia - Wardah Awwalin Ikhsaniah Saldi; Fajri Adrianto; Masyhuri Hamidi (International Journal Labs, 2023)
The purpose of this paper is to determine the effect of environmental, social and corporate governance (ESG) performance on company dividend policy in Indonesia. This paper uses three controlled variables: firm size, firm age, and firm leverage. The data used in this research are secondary data from Thomson Reuters Eikon Database on 17 companies listed on the Indonesian Stock Exchange over 2011-2020. To analyze the data, this research uses Panel Data Regression Analysis with Common Effect Model aided by STATA 17. The results show that Environmental, Social and Corporate Governance performance has a positive and significant effect on company dividend policy in Indonesia. This paper adds value to the existing literature as it provides an overview of the impact of Environmental, Social and Corporate Governance, especially in relation to the performance of companies Indonesia. It can therefore provide a good basis for understanding of how Indonesian companies can be more appealing to investors.